Avaliação do potencial antioxidante, antimicrobiano e toxicológico do extrato da farinha da casca da jabuticaba (Plinia cauliflora) - Araújo, Lucas Francelino de (2017)
The presence of bioactive compounds in tropical fruits leads to an increase in their consumption and their agroindustrial waste processing products and the interest in research associated with the use of residues. Plinia cauliflora popularly known as jabuticaba is a fruit originating in Brazil and its bark represent up to 43% of the fruit. The objective of this study was to evaluate the antioxidant activities (DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS [2,2'-azino-bis (3-ethylbenzothiazoline) 6-sulfonic acid]), antimicrobial of disc diffusion method and minimum inhibitory concentration and toxicity in Danio rerio embryos of the peel and flour peel extracts of Plinia cauliflora. In order to carry out these analyzes, the peels were separated into two lots: peel in natura (lot 1) and peel flour (lot 2), both of which were extracted with ethyl alcohol (99.5%), extracts from each batch. In the antioxidant and antimicrobial activity, the peel flour and the peel in natura presented similar results among themselves, a fact explained by the low temperature used (40 ° C) in the drying process, in which it was not directly affect the bioactive compounds in its plant matrix . It was also observed that the extract of the peel flour did not present toxic potential in concentrations equal to or less than 2.5 μL / mL in Danio rerio embryos. Therefore, the use of peel flour extract from Plinia cauliflora to industry can be a safe, promising and sustainable alternative of added quality to a higher value to final products.